Analisa Kinerja Dosen dalam Pelaksanaan Tridharma Perguruan Tinggi dengan Metode Balance Scorecard - Ika Endrawijaya; Eriyandi Eriyandi; Hendro Widiarto (Departement of Mathematics Education, 2024)
This research explores the performance of lecturers at the Indonesian Aviation Polytechnic (PPI) Curug, a state-owned higher education institution under the Ministry of Transportation of the Republic of Indonesia, mandated to carry out the three pillars of higher education. The quality of education is identified through the evaluation of lecturers' performance in fulfilling their duties. The research aims to measure lecturers' performance using the Balance Scorecard method, highlighting four key perspectives: internal process, financial, customer, and learning and growth. Data were obtained through the analysis of administrative documents from PPI Curug and a survey of students. The results show a high level of satisfaction from students regarding lecturers' performance, particularly in aspects of teaching techniques, mastery of materials, punctuality, and the organization of lectures. Although the lecturers' performance is positively assessed in internal process, financial, and customer perspectives through the Balance Scorecard approach, there is a need for improvement in the learning and growth perspective to ensure sustainable development.